2021
DOI: 10.1111/1442-1984.12331
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific competition favors ant–plant protective mutualism

Abstract: The dependency of the anti‐herbivore defense on ant–plant protective mutualism often varies depending on abiotic and biotic conditions. Although intraspecific competition is a primary interaction between neighboring plants, its effects on ant–plant mutualisms have yet to be sufficiently elucidated. In order to determine the effects of intraspecific competition and competitor genotype on ant–plant mutualisms, I conducted competition and ant‐removal experiments and examined their effects on damage to the leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Local population density of host plants likely affects host plant quality, because it is linked to the interaction environment: host plants present at high density are exposed to direct intraspecific interaction, whereas host plants present at low density are exposed to direct interspecific interaction or no interaction. Many studies have reported that plant–plant direct interactions influence leaf traits (Barton & Bowers, 2006; Mraja et al., 2011; Muiruri et al., 2019) and herbivory (Hambäck & Beckerman, 2003; Muiruri et al., 2019; Yamawo, 2021). For example, plant competition for resources induces plastic changes in the plants' resource allocation; these changes can affect root or shoot growth.…”
Section: Introductionmentioning
confidence: 99%
“…Local population density of host plants likely affects host plant quality, because it is linked to the interaction environment: host plants present at high density are exposed to direct intraspecific interaction, whereas host plants present at low density are exposed to direct interspecific interaction or no interaction. Many studies have reported that plant–plant direct interactions influence leaf traits (Barton & Bowers, 2006; Mraja et al., 2011; Muiruri et al., 2019) and herbivory (Hambäck & Beckerman, 2003; Muiruri et al., 2019; Yamawo, 2021). For example, plant competition for resources induces plastic changes in the plants' resource allocation; these changes can affect root or shoot growth.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible hypothesis is that Aggregated plants invest more in defence than do Solitary plants through recognition of con-specific neighbours, because aggregated plants often consumed by specialist leaf beetles. Leaf-trait alteration based on neighbour recognition has also been reported in several plant species (Yamawo & Mukai 2020;Yamawo, 2015Yamawo, , 2021. Neighbour recognition can therefore be a cause of leaf-trait alteration in R. obtusifolius plants.…”
Section: Variations In Leaf Traitsmentioning
confidence: 85%
“…Therefore, variations in the interaction environment induce changes in expression of the chemical traits of host plant leaves (Barton & Bowers, 2006;Broz et al, 2010;Mraja et al, 2011;Muiruri et al, 2019), so they are likely to influence leaf herbivory and the distribution of herbivores. In fact, several studies have strongly suggested that changes in leaf traits in response to differences in the interaction environment of host plants influence herbivory or herbivore distribution (e.g., Broz et al 2010;Muiruri et al, 2019;Yamawo, 2021). However, to our knowledge, no experimental evidence has yet been provided for this effect.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations